Simulation of Dimple Characteristics on the Trajectories of a Dimpled Sphere (Golf Ball) in Motion - Wainaina, M; Kimathi, M; Malonza, D (My University, 2018)
A mathematical model describing the flight motion of a golf ball is developed, and the effects of dimple characteristics are studied. Using the Newton’s second law of motion, the equations governing the motion of the golf ball are developed in three dimensions. In this development the size, depth and number of dimples are taken into account. By varying the dimple size, depth and number, the effects of these characteristics are simulated via a MatLab code in which the Dormand-Prince Runge Kutta method is implemented to solve the model equations. The results of the numerical simulations that show how the golf ball trajectory is influenced by the dimple characteristics such as dimple depth, size and number within the accepted range of the Reynolds number are displayed and discussed.
Keywords: Dimple; Trajectories; Boundary layer; Reynolds’s number